Teaching collaboration and feedback supported by CLIL as a development to the pre-service teacher identity (2024)
This research article explores the influence of collaborative peer work and feedback on teacher identity development within a CLIL (Content and Language Integrated Learning) framework. Based on qualitative methods, we examine how pre-service and in-service teachers engage in collaborative materials design and reflective practices to enhance their professional growth. Results reveal that collaboration fosters reflective teaching, strengthens teacher agency, optimizes lesson planning and classroom effectiveness, leading to progress in student outcomes. Moreover, feedback plays a key role in helping teachers identify areas for correction and refine their strategies, contributing to a stronger professional identity. Finally, through peer collaboration, teachers exchange ideas and develop adaptive approaches to various classroom challenges. In summary, the study underscores the importance of collaborative and feedback environments in shaping teacher identity, promoting professional development, and enhancing the quality of teaching in the context of CLIL and English language teaching.